Tasks, The Implementation of Which Will Ensure the Food Security of the Republic of Uzbekistan (Texas Journal of Agriculture and Biological Sciences, 2023)
The article tells about the new agrarian policy in the Republic of Uzbekistan, about new approaches to financing the developing agro-industrial complex. Timely state reforms and strategic planning in the field of attracting investments in the agrarian sector of the Republic.